The Relationship Between Health Education and Knowledge Elderly People About Hypertension at the Sayur Matua Elderly Posyandu, Saran Padang Village, Simalungun Regency - Marbun, Meyana; Purba, Yeni Trisna; Febiola, Marcellyn (PT Inovasi Pratama Internasional, 2023)
Hypertension is the leading cause of heart failure, stroke, and kidney failure. Hypertension is a risk factor for morbidity and mortality, influenced by emotional disturbances, obesity, excessive alcohol consumption, excessive coffee consumption, and heredity. The majority of respondents were aged 65–70 years (38.4%), while a minority were aged over 70 years (30.3%). The majority of respondents were female (67.7%), while a minority were male (32%). The majority of respondents have jobs as retired civil servants, namely 23 people (23.2%), traders/entrepreneurs, namely 23 people (23.2%), farmers, namely 23 people (23.2%), while the minority are private employees, namely 12 people (12.2%). The majority of respondents have junior high school education, namely 36 people (36.4%), high school education, namely 36 people (36.4%), while the minority have college education, namely 13 people (13.1%). The majority of respondents have received health education, namely 54 people (54.5%), while the minority have never received health education, namely 45 people (45.5%). The majority of respondents have sufficient knowledge, namely 44 people (44.4%), while the minority have insufficient knowledge, namely 20 people (20.2%). From the results of the chi-square test of the cross-table of health education with knowledge, the p value is 0.000. It can be concluded that health education has a relationship with the knowledge of the elderly about the relationship of health education with the knowledge of the elderly about how to prevent hypertension at the Sayur Matua Elderly Posyandu, Saran Padang Village, Dolok Silau District, Simalungun Regency in 2020, because the p value <0.05.